A construção da carreira docente no sistema municipal de ensino de Rio Claro: profissionalização e valorização profissional - Souza, Jeferson Mello [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research or study had purpose to analyse the Teacher's Career building in the Teaching Municipal Network in Rio Claro City: professionalism and occupation valorization.The presupposition is just that the teaching career constituted in one of the indicator for the teachership's valuation policy defended by the Ministry of Public Instruction and Cultural Development (=MEC). For the realization of the proposed study, they decided to developing a qualitative boarding through the bibliographical statistics area and documental analysis, forming a compact historical trajectory of the teacher's career in Brazil. Therefore, it was realized a careful analysis of the context/revision of the Legislation that bases upon the teacher's career for the implantation of Public Politics of Teachership Valorization in Federal and Municipal sphere, and that, culminated for the creation of the Plan of Career in Rio Claro Municipal City. In order to make possible the concretion of the proposition at issue or in question, it was also analysed the procedure of construction of the First Statute of Municipal Public Teachership = Law nº 2.081, from October 31 st, 1986, as well as the Actual Statute, which is based upon in Law nº 24, from October 15th, 2007 and in the Law nº 3.777, from October 15th, 2007, that established the Status/Function, Career and Plan of Salaries for the Municipal Public Teachership in Rio Claro City, in searching for comprehending if the Municipal Education Secretaryship have pomoted the Teaching Staff's Valorization belonged to Teaching Municipal Network, starting from the argument from how the Teaching Career is being built/structured, in the sense to note if in fact, there is the Teaching Staff Valorization. The research or study shows cleary the reality scenery of the Teaching Staff Career in Rio Claro City, through an observing realization from the historical development of the Schools, the process of characterizing from the ...

Este estudo teve por objetivo analisar A Construção da Carreira Docente no Sistema Municipal de Ensino de Rio Claro-SP: profissionalização e valorização profissional. O pressuposto é o de que a carreira docente se constitui em um dos indicadores da política de valorização do magistério defendida pelo Ministério da Educação (MEC). Para a realização do estudo proposto, optou-se por desenvolver inicialmente uma abordagem qualitativa, com levantamento bibliográfico da área e análise documental, construindo um breve histórico do percurso da carreira docente no Brasil. Para tanto, foi realizada uma revisão da legislação que embasa a carreira docente para a implantação de Políticas Públicas de Valorização do Magistério Público, em âmbitos federal e municipal, que culminou na criação do Plano de Carreira no município de Rio Claro-SP. A fim de possibilitar a concretude da proposição em questão, foi analisado, também, o processo de construção do primeiro Estatuto do Magistério Público Municipal - Lei nº 2.081 de 31/10/1986, assim como o atual, que está embasado na Lei Municipal nº 024 de 15/10/2007, e na Lei nº 3.777 de 15/10/2007 que instituíram o Plano de Cargos, Carreira e Vencimentos do Magistério Público Municipal de Rio Claro, na busca por compreender se a Secretaria Municipal de Educação tem promovido a valorização profissional dos docentes pertencentes ao Sistema Municipal de Ensino, a partir do questionamento de como vem sendo construída sua carreira docente, no sentido de perceber se de fato há valorização docente. O estudo evidencia o cenário da realidade da Carreira Docente em Rio Claro-SP, mediante realização do mapeamento do histórico das escolas, da caracterização do perfil dos docentes, da demonstração dos avanços e percalços em relação aos direitos trabalhistas que perpassaram a construção da carreira docente. Os resultados da pesquisa indicaram que o Sistema...
Keywords: Teachers, Training of; Professores - Formação; Ensino - Legislação; Qualificações profissionais; Direito do trabalho; Rio Claro (SP)